"It's Better to Sweat than to Die:" Rural-to-Urban Migration, Northern Karamoja, Uganda (Tufts Archival Research Center, 2018)
"It's Better to Sweat than to Die:" Rural-to-Urban Migration, Northern Karamoja, Uganda, by Elizabeth Stites, John Burns, and Darlington Akabwai